2011
DOI: 10.1097/ajp.0b013e31821d904c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Pain Hypersensitivity in Schizophrenic Patients

Abstract: Under these conditions, schizophrenic patients were hypersensitive to pain induction compared with normal individuals. The hypoalgesia typically associated with schizophrenic patients may correspond to fewer than normal reports of pain, rather than to impaired sensations of pain. This should be taken into account during routine medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 55 publications
0
35
0
1
Order By: Relevance
“…Reduced pain expression (which might be mistaken for reduced pain sensitivity) has also been put forward as a marker of "hypofrontality" in schizophrenia (Bonnot et al 2009 ;El-Mallakh et al 2005 ). However, the association between clinical symptoms of schizophrenia and pain has not consistently been found (Girard et al 2011 ).…”
Section: Symptoms Of Schizophrenia and Comorbid Psychiatric Symptomsmentioning
confidence: 98%
See 2 more Smart Citations
“…Reduced pain expression (which might be mistaken for reduced pain sensitivity) has also been put forward as a marker of "hypofrontality" in schizophrenia (Bonnot et al 2009 ;El-Mallakh et al 2005 ). However, the association between clinical symptoms of schizophrenia and pain has not consistently been found (Girard et al 2011 ).…”
Section: Symptoms Of Schizophrenia and Comorbid Psychiatric Symptomsmentioning
confidence: 98%
“…Merely considering experimental and case studies might not fully represent pain in schizophrenia. Abilities such as a fast response and an adequate expression of pain might be impaired in people with schizophrenia, consequently biasing results (Girard et al 2011 ). Pain reaction might also depend on the type of experimental manipulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are studies that prove the absence of any differences between normal group and schizophrenic patients [21], Strassnig and collaborators claim that people suffering from schizophrenia feel pain at a higher level [22,23]. Another research that sustains the Strassnig hypothesis is made by Girard and collaborators who tested tolerance to pain in similar medical conditions and noticed hypersensitivity to pain in schizophrenic patients [24,25]. Consequently, taking into account all the research regarding pain in schizophrenia one thing is certain, altered pain perception is a fact in schizophrenic disorder [26].…”
Section: Pain and Schizophreniamentioning
confidence: 98%
“…Thermal, electrical, cold and tactile stimulation have been utilized to assess pain threshold and pain tolerance in schizophrenia [8][9][10][11]. A significant part of these experimental pain studies concluded that persons with schizophrenia appear to be less sensitive to pain compared to healthy controls.…”
Section: Symptoms Of Schizophreniamentioning
confidence: 99%